Ferriakasakaite-(La) and ferriandrosite-(La): new epidote-supergroup minerals from Ise, Mie Prefecture, Japan. (2nd January 2018) - Nagashima, Mariko; Nishio-Hamane, Daisuke; Tomita, Norimitsu; Minakawa, Tetsuo; Inaba, Sachio
Abstract: The new REE -rich, monoclinic, epidote-supergroup minerals ferriakasakaite-(La) and ferriandrosite-(La), found in tephroite calcite veinlets cutting the stratiform ferromanganese deposit from the Shobu area, Ise City, Mie Prefecture, Japan, were studied using electron microprobe analysis and single-crystal X-ray diffraction methods. Ferriakasakaite-(La), ideally A 1 Ca A 2 La M 1 Fe 3+ M 2 Al M 3 Mn 2+ (SiO4 )(Si2 O7 )O(OH) ( Z = 2, space group P 21 / m ), has a new combination of dominant cations at A 1 (Ca) and M 3 (Mn 2+ ), which are the key sites to determine a root name for epidote-supergroup minerals. The unit-cell parameters are a = 8.8733(2), b = 5.7415(1), c = 10.0805(3) Å, β = 113.845(2)° and V = 469.73(2) Å 3 . According to the structural refinement ( R 1 = 3.13%), the determined structural formula is A 1 (Ca0.54Mn2+0.46) A 2 [(La0.48 Ce0.20 Pr0.07 Nd0.18 Gd0.02 )Σ0.95 Ca0.05 ] M 1 (Fe0.42 3+ V0.34 3+ Al0.18 Ti0.06 4+ ) M 2 (Al0.96 Fe0.04 3+ ) M 3 (Mn0.50 2+ Fe0.43 2+ Mg0.07 )(SiO4 )(Si2 O7 )O(OH). Ferriandrosite-(La), ideally A 1 Mn 2+ A 2 La M 1 Fe 3+ M2Al M 3 Mn 2+ (SiO4 )(Si2 O7 )O(OH) ( Z = 2, space group P 21 / m ), is the M 1 Fe 3+ analogue of androsite. The unit-cell parameters are a = 8.8779(1), b = 5.73995(1), c = 10.0875(2) Å, β = 113.899(1)° and V = 469.97(2) Å 3, and the structural formula is A 1 (Mn0.56 2+ Ca0.44 ) A 2 [(La0.49 Ce0.20 Pr0.08 Nd0.19 Gd0.02 )Σ0.97Ca0.03] M 1 (Fe0.40 3+ V0.28 3+ Al 0.20 Fe0.05 2+ Ti0.07 4+ ) M 2 (Al0.97 Fe0.03 3+ ) M 3 (Mn0.50 2+ Fe0.40 2+ Mg0.10 )(SiO4 )(Si2 O7 )O(OH) ( R 1 = 2.93%). The two new minerals, which are compositionally very similar overall, are distinguished by occupancy of A 1, Ca vs . Mn 2+ . The structural properties of these minerals depend not only on the REE content at A 2, but also on the Mn content at A 1 .